Ireland's external assets - Whitaker, T. K. (Statistical and Social Inquiry Society of Ireland, 1949)
The term ?external assets? as applied to holdings by Irish people abroad would be misleading if it conveyed the impression of a diversity of holdings in different currencies. In fact, over 97% of these external assets are in sterling. The primary explanation for this is, of course, that Ireland's earnings abroad are virtually all sterling earnings. About 90% of Irish exports are consigned to the United Kingdom and most of Ireland's invisible income?from tourism, pensions, remittances, etc, as well as investments?comes from the United Kingdom.
Read before the Society, 29 April 1949
Keywords: Ireland -- External wealth; Ireland -- External assets; Ireland, 1945- -- Economy; 314.15